Jean-Pierre Camus : la moralisation d’un genre immoral est-elle possible ? - Pawłowska, Maja (Quêtes littéraires, 2013)
Camus complements his novels with long peritexts, thus using his ecclesiastic authority to legitimise their moral and didactic value. In these peritexts he juxtapposes the licentious novels with his own devout works of fiction, which are, in his own words, not only valuable and worth recommending, but also capable of saving the readers’ souls, put in danger by other texts. In any case, a close reading of these peritexts reveals a view which challenges the idea of the novel’s insidiousness and which bears witness to Camus’s great fascination with this officially condemned literary genre.